Variables that Affect Customer Satisfaction of Online Food Delivery Service Users - Indrayani, Rina; Muhammad, Ashrul Adi (Green Publisher Indonesia, 2022)
Improving the quality of service is the most important thing for service companies, as is the case with PT. Gojek Indonesia as one of the online-based service provider companies, customer satisfaction is very important to know the level of satisfaction and quality of service to customers. The development of electronic service quality in online-based service providers was carried out by distributing questionnaires to 385 respondents to determine the effect of electronic service quality on the satisfaction of consumers who use it, as well as finding proposals for improvements in electronic services based on the right dimensions of e-servqual. In improving the quality of online-based food delivery services, the development of an E-Service Quality (E-Servqual) model was carried out which was built using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method in the form of 10 dimensions of electronic service quality, namely ease of use, website design, customization, responsiveness, assurance assurance, reliability, tangible, emphaty, price, and customer value. The results of the study found that the dimensions that accommodate the quality of electronic services for online food delivery services are variables of customer value, reliability, assurance, emphaty, website design, tangible, responsiveness, and price, but there is 1 variable that does not have a significant effect on satisfaction consumers i.e. variable prices. While the results of simultaneous testing, all variables formed in the final model have a significant effect on consumer satisfaction, so that the development of the e-servqual model in services online-based food delivery services are declared optimal.